A supercyclone, landscapes of 'emptiness' and shrimp aquaculture: The lesser-known trajectories of disaster recovery in coastal Odisha, India. (May 2022) - Chhotray, Vasudha
Highlights: Reconfiguration of paddy growing landscape after a supercyclone in Odisha to commercial aquaculture backed by the state and private capital. Transformation based on a powerful shared narrative of the landscape rendered empty and unproductive by the supercyclone. This narrative is misleading and obliterates previously disastrous attempts at shrimp culture, to the detriment of poor farmers. Experience of aquaculture reveals new forms of precarity and differentiation, and the lack of regulation and support by the state. Disaster recovery as long-term transformation left to capitalist development; state pursues a techno-infrastructural response strategy. Abstract: This paper critically examines the reconfiguration of post-supercyclone Ersama in coastal Odisha in India, to encourage the introduction of a new form of shrimp aquaculture as the principal livelihood. It demonstrates the operation of a powerful shared construction of Ersama, a typically paddy cultivating area, as a landscape rendered 'empty' and 'unproductive' by the supercyclone of 1999. The paper shows how this notion, shared by locals and external actors, facilitates the entry of the forces of commercial aquaculture at the cost of increased socio-economic inequalities and risk-taking for the poorest participants, as well as the exclusion of women from this new livelihood. Memories of previous disastrous attempts at shrimp culture are obliterated through misleading narratives about the potent productivity of a new type of shrimp by the proponents of aquaculture. The state has presided through uneven regulation, disregarding the damaging effects of commercial aquaculture for the coastal environment. The paper argues that besides the provision of disaster relief, the state restricts its own responsibilities towards disaster prone and affected populations to the creation of warning systems and physical infrastructures. However, it assigns the broader challenge of disaster recovery to ongoing processes of capitalist development. Even as the resulting precarity, both economic and environmental, threaten long-term and inclusive recovery, the state delinks disaster recovery from questions of structural risk resulting from exclusionary development pathways, depoliticising it considerably.